Ultraestructura del bambú Guadua angustifolia var. bicolor (Poaceae: Bambusoideae), presente en Costa Rica - Montiel, Mayra (2006)
The anatomy of several parts of Guadua angustifolia var. bicolor was analyzed and characterized under a scanning electron microscope. Many similarities were observed with other Guadua species, particularly the presence of high dome stomata, of large cells with sinuous walls and of silica cells. Specific bicolor characteristics include (1) a different stomatal pattern in the adaxial zone of the leaf base (close to the sheath); (2) the abundance of hook-shaped trichomes without papilla; (3) the distinctive golden brown color of the bract that covers the culm (caused by papillar trichomes that cover the adaxial sheath); and (4) the size of the groups of auricular trichomes (formed by 12 trichomes). Rev. Biol. Trop. 54(Suppl. 2): 13-19. Epub 2006 Dec. 01.